Bending Test of Rectangular High-Strength Steel Fiber-Reinforced Concrete-Filled Steel Tubular Beams with Stiffeners - Shiming Liu; Zhaoyang Ji; Shangyu Li; Xiaoke Li; Yongjian Liu; Shunbo Zhao (Buildings)
To better understand the bending performance of rectangular high-strength steel fiber-reinforced concrete (HSFRC)-filled steel tubular (HSFRCFST) beams with internal stiffeners, ten beams were subjected to a four-point bending test. The primary considerations were the strength grade of the HSFRC, the steel fiber content, the internal stiffener type, and the circular hole spacing of the perfobond stiffener. The moment–curvature and flexural load–deflection curves were calculated. The mode of failure and the distribution of cracks of the infill HSFRC were observed. The presence of steel fibers greatly improved the bending stiffness and moment capacity of HSFRCFST beams, with the optimal effect happening at a steel fiber content of 1.2% by volume, according to the experimental findings. The type of stiffener influenced the failure modes of the exterior rectangular steel tube, which were unaffected by the compressive strength of the infill HSFRC. On the tension surface of HSFRCFST beams, the crack spacing of the infill HSFRC was virtually identical to the circular hole spacing of perfobond stiffeners. When the circular hole spacing was between two and three times the diameter, the perfobond stiffener worked best with the infill HSFRC. The test beams’ ductility index was greater than 1.16, indicating good ductility. The test beams’ rotational capacities ranged from 6.26 to 13.20, which were greater than 3.0 and met the requirements of the specification. The experimental results demonstrate that a reasonable design of the steel fiber content and the spacing between circular holes of perfobond stiffeners can significantly improve the bending resistance of rectangular HSFRCFST beams. This provides relevant parameter design suggestions for improving the ductility and bearing capacity of steel fiber-reinforced concrete beams in practical construction. Finally, a design formula for the moment capacity of rectangular HSFRCFST beams with stiffeners is presented, which corresponds well with the experimental findings.